Measuring Hope Among Children Affected by Armed Conflict: Cross-Cultural Construct Validity of the Children's Hope Scale. (June 2017) - Haroz, Emily E.; Jordans, Mark; de Jong, Joop; Gross, Alden; Bass, Judith; Tol, Wietse
We investigated the cross-cultural construct validity of hope, a factor associated with mental health protection and promotion, using the Children's Hope Scale (CHS). The sample ( n = 1, 057; 48% girls) included baseline data from three cluster-randomized controlled trials with children affected by armed conflict ( n = 329 Burundi; n = 403 Indonesia; n = 325 Nepal). The confirmatory factor analysis in each country indicated good fit for the hypothesized two-factor model. Analysis by gender indicated that configural invariance was supported and that scalar invariance was demonstrated in Indonesia. However, metric and scalar invariance were not supported in Burundi and Nepal. In country comparisons, configural and metric invariance were met, but scalar invariance was not supported. Evidence from this study supports the use of the CHS within various sociocultural settings and across genders, but direct comparisons of CHS scores across groups should be done with caution. Rigorous evaluations of the measurement properties of mental health protective and promotive factors are necessary to inform both research and practice.